STRATEGI PENANGANAN ANAK BERHADAPAN DENGAN HUKUM MELALUI UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Nurul Farida (Jurnal Magister Hukum Perspektif, 2020)
The deviation of the behavior of today's children has crossed the appropriate limit. Many children begin to indulge in casual sex, narcotics, violence, thuggery, and many more actions that can be categorized as unlawful. The Law mandates that children are a gift of God Almighty who has the dignity and dignity as a full human being, and therefore, they are entitled to special protection, especially legal protection in the judicial system by providing special protection to children who face the law. The Indonesian Child Protection Commission (KPAI) stated that the number of children facing the law (ABH) is increasing year on year. Nevertheless, in accordance with UNICEF's mandate, the involvement of children in criminal justice for adults can hurt children, both psychologically and socially. The formulation of the problem in this writing is "What is the strategy for handling ABH through Law No. 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA)?" The method used is an empirical juridical method with a sociological approach, which seeks to review the application of the SPPA Law in the handling of ABH. The results of the review showed that there are several factors that cause ABH, namely instrinsic and extrinsic factors. To protect children's rights, ABH handling strategies can be used in accordance with the SPPA Law, namely by using restorative justice and diversion efforts. Obstacles faced in the implementation of ABH handling strategies include the lack of socialization of laws and regulations related to children so that the understanding of law enforcement officials in the implementation of ABH handling is still varied and tends to use different perceptions. Keywords: Strategy, Juvenile Criminal Justice System, Restorative Justice, Diversion